Factors influencing perinatal outcome in eclampsia at a tertiary referral hospital - Sathyanarayana, Chaitra; Somanna, Radhamani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Perinatal mortality in eclampsia still continues to be high in developing countries mainly due to prematurity and birth asphyxia. This study was conducted at a tertiary referral hospital to analyse the perinatal outcome in eclampsia and identify the associated risk factors. Methods: A prospective study wherein 170 cases of eclampsia admitted to Cheluvamba Hospital, Mysore, India over a period of one and half years were analysed. Results: The incidence of eclampsia was 1.08%. 88.8% of the cases were delivered vaginally and 8.2% by LSCS. Majority of the babies (48.8%) weighed between 1000-2000 gms. The perinatal mortality rate in this study was 55.3%. Prematurity (61%), SGA (55%) and birth asphyxia (55%) were the most common causes of perinatal morbidity. Birth asphyxia was the commonest cause of perinatal death (51.2%) followed by respiratory distress syndrome (20.93%), septicemia (13.95%) and meconium aspiration syndrome (6.98%). Jaundice, pulmonary hemorrhage and intracranial hemorrhage contributed to 2.33% of early neonatal deaths each. Among various probable risk factors for poor perinatal outcome, BP ≥160/110 mmHg, gestational age <28 weeks, vaginal route of delivery, antepartum eclampsia and convulsion delivery interval ≥24 hours were associated with significantly higher perinatal mortality (p < 0.05). Conclusions: Strict fetal monitoring and prompt timely intervention may help to reduce the perinatal mortality rate. The NICU facilities have to improve especially in government hospitals so that smaller babies can be taken care of and salvaged.